ANALISIS PENERAPAN STANDAR AKUNTANSI KEUANGAN SYARIAH PADA KOPERASI SYARIAH BMT AL ISHLAH KOTA JAMBI - Ridwan, Ridwan; Khairiyani, Khairiyani (Yayasan Nusantara Hasana Berdikari, 2025)
Sharia accounting is a process of accounting activities based on sharia principles (Islam) and is accountable to Allah SWT. This accounting is needed to support activities that must be carried out in accordance with sharia, because it is impossible to implement sharia-compliant accounting if the accounting process is not sharia (conventional). The BMT AL ISHLAH Cooperative in Jambi City is one of the sharia-based microfinance institutions. This cooperative is under the supervision of the Minister of Cooperatives and SMEs. including the Sharia Savings and Loans and Financing Cooperative (KSPPS). The researcher uses a qualitative research method where qualitative research is research that requires data and information directly to the field or research location. Qualitative research makes the researcher a key (main) instrument where the researcher will collect data, check the validity of the data, and analyze the data. The data source used by the author uses secondary data. secondary data is data obtained or collected by other people or certain institutions that are more informative. Therefore, researchers want to see how the application of sharia accounting standards in financial reports is based on PSAK 101 and murabahah financing based on PSAK 102.